PENGUATAN MODERASI BERAGAMA BERBASIS DIGITALISASI MANUSKRIP DI PESANTREN AL ASROR TULUNGAGUNG - Hibbi Farihin; Nurul Setyawati Handayani; Rizal Zamzami; Nurul Baiti Rohmah; Intan Sari Dewi; Ahmad Fauzan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The community service activity “Strengthening Religious Moderation Based on Manuscript Digitization at Pesantren Al Asror Tulungagung” was held on Friday-Saturday, November 8-9, 2024, and was attended by 50 participants from Al Asror Kedungwaru Islamic Boarding School, Tulungagung. The activity was carried out with the stages of providing material about religious moderation and its implications in everyday life providing knowledge and practicing how to process manuscripts for digitization. In implementing this service, it is packaged with lecture, discussion, and question and answer methods and provides skills on manuscript digitization. This activity deepened participants' understanding and attitudes regarding religious moderation in everyday life and manuscript digitization skills as a solution to processing and transferring manuscripts in Islamic boarding schools.